Experiences, problems and solutions in computer usage by subjects with Tetraplegia - Medola, Fausto O. [UNESP]; Lanutti, Jamille [UNESP]; Bentim, Claudia G.; Sardella, Adrieli [UNESP]; Franchinni, Ana Elisa [UNESP]; Paschoarelli, Luis C. [UNESP] (Springer Nature, 2015)
For the vast majority of users, the most conventional means of interaction with a computer is through the use of the keyboard and the mouse. The act of typing and clicking in a satisfactory speed requires a level of motor ability and coordination, which is provided by the integration of both sensory and neuromotor functions. Among many neurological problems that may affect movement control, tetraplegia due to spinal cord injury challenges the subject to adopt to a severe sensory-motor impairment of the lower limbs, trunk and partial or total affection of the upper limbs. Therefore, tetraplegia represents an important limitation for the user in his/her ability to interact with a computer in a satisfactory and conventional way (keyboard-typing and mouse-clicking). This paper aims to investigate the experiences, problems and solutions used by persons with tetraplegia due to spinal cord injury in daily computer usage. The study sample was comprised by five with tetraplegia due to spinal cord injury. All the subjects had a certain degree of function in the upper limbs, and their levels of injury were between C5 and C7 (fifth to seventh spinal cord segment). A questionnaire with multiple-choice questions about subjects’ interaction with computers in daily usage was applied. The questions aimed to understand their experiences and problems when using a computer (typing, clicking and printing, among others), as well as the use of assistive devices aimed to facilitate the computer usage. Prior to the study, all subjects were informed about the study objectives and procedures, and signed an informed consent form after agreeing in participate in the study. Ethical approval was obtained from the Ethical Committee of the Faculty of Architecture, Arts and Communication - UNESP. The results show that subjects with tetraplegia experience a number of problems when using a computer. These problems occur with the use of all the computer components, such as keyboard, mouse, cables and accessories. The severe upper limb impairment is, ultimately, the main factor that limit the users’ ability to use a computer in an indepen\dent and efficient way. The current study contributes to the knowledge in the fields of ergonomics, design and assistive technologies, as it highlights the need of providing assistive solutions that truly contribute to the satisfactory use of computers by subjects with tetraplegia.
Keywords: Assistive technologies; Ergonomics; Human-computer interface; Tetraplegia